Advanced development of dairy farm waste-based biocarbon-reinforced unsymmetrical structured bio-phenolic polybenzoxazine composites. (February 2021) - Selvaraj, V; Raghavarshini, TR; Alagar, M
In the present work, an attempt has been made to develop cow manure carbon-reinforced hybrid biophenol-based benzoxazine composites for antifouling coating applications. Bio-based benzoxazine with unsymmetrical molecular structure was synthesized using the mixture of a combination of cardanol and eugenol with diaminodiphenyl methane and paraformaldehyde, and the hybrid-benzoxazine obtained was characterized using different analytical techniques, viz., Fourier transform infrared, nuclear magnetic resonance and MALDI mass. Bio-based benzoxazine was further reinforced with varying weight percentages (1, 3 and 5 wt%) of biocarbon derived from cow manure to obtain hybrid composite coatings. The hybrid benzoxazine matrix and composites were studied for their thermal behaviour, contact angle (CA), morphology, corrosion-resistant behaviour and antifouling character to utilize them as coatings materials for different industrial applications. Results obtained from different studies inferred that the biocarbon-reinforced composites possess an enhanced value of glass transition temperature (249°C), high char yield (38.4%), improved CA (105.6°), higher efficiency of corrosion protection against mild steel surface (98%) and improved antimicrobial activity.